Water Mediated Condensation Reaction Of Aldehydes And Amines - NEERJA GUPTA; RUBY NAAZ; G.D. NIGAM (International Journal of Pharma and Bio Sciences, 2010)
The condensation reactions of aliphatic and aromatic aldehydes and amines carried out efficiently in a water suspension medium. The formation of imines and imidazoles are carried out without catalyst using water as solvent. In this method yields are high, reactions are fast and products are isolated easily by filtration.